Effects of pretreatments on drying rate, physico-chemical, and capsaicin content of dried chili pepper (capsicum frutescens l.cv.labuyo) - Lascano, Jenny Mae V.
ABSTRACT This study aimed to determine the effects of pretreatments on drying rate, physicochemical properties, and capsaicin content of dried chili pepper (Capsicum frutescens l. cv. Labuyo). Pretreated samples were dried in a conventional cabinet dryer at a 65°C drying temperature. Moisture content, water activity (aw), pH, and color were determined using the AOAC methods. The SHU and capsaicin content of dried chili flakes were obtained using Scoville Test. Experimental drying rate curves were established and showed that the drying process mainly occurred in the falling rate period. Chili peppers water blanched for three minutes showed the longest drying time while chili peppers soaked in 0.6% ascorbic acid showed the shortest drying time. Moreover, based on the drying curves, chili peppers pretreated with ascorbic acid had the lowest final moisture content. Water activity and pH of dried samples generally decreased compared to Aw and pH of fresh chili peppers. Water blanching for three minutes provided the lowest moisture content after drying. Color measures showed that the most effective pretreatment are three-minute water blanching in terms of total color change (ΔE); soaking in 0.4% ascorbic acid in terms of redness to yellowness ratio (R) and Browning Index (BI); and soaking in 0.6% ascorbic acid in terms of hue angles (h°) and chroma values (C). Chili peppers water blanched for one minute and steam blanched for two minutes had the highest capsaicin content and SHU among all pretreated samples.